(untitled) (Research, Society and Development, 2020)
The global impacts on public health and the economy caused by the COVID-19 pandemic highlighted the weaknesses of crisis and emergency preparedness systems for both the State and companies. Work, employment and income were notably affected and insecurity for the future due to economic losses, fear of contagion, changes in routine and increased environmental stressors affected workers, especially health professionals on the front lines of fighting the pandemic. This article aims to discuss the impacts of COVID-19 on the work and mental health of health workers. To this end, the production of the most recent knowledge about the impacts of COVID-19 on work and income and its relationship with evidence of symptoms of mental health problems among workers, especially health professionals, were analyzed. This is an integrative literature review, supported by international databases, reports by international agencies and relevant legislation. The results demonstrate that the prolonged exposure to the pathogenic agent, fear of contagion, intensive working hours, environmental and occupational stressors, the need to deal with the psychological demands of patients and the ethical dilemmas in decision making make health professionals susceptible to loss of quality of life during and after the pandemic.